Electrocatalytic Reduction of Nitrate via Co3O4/Ti Cathode Prepared by Electrodeposition Paired With IrO2-RuO2 Anode - Wang, Chuan; Cao, Zhifen; Huang, Hongtao; Liu, Hong; Wang, Sha (Frontiers in Chemistry, 2022)
Nitrate pollution is already a global problem, and the electrocatalytic reduction of nitrate is a promising technology for remediation of wastewater and polluted water bodies. In this work, Co3O4/Ti electrodes were prepared by electrodeposition for the electrocatalytic reduction of nitrate. The morphology, chemical and crystal structures of Co3O4/Ti and its catalytic activity were investigated. Then, the electrocatalytic nitrate reduction performance of Co3O4/Ti as the cathode was evaluated by monitoring the removal efficiencies of nitrate (NO3--N) and total nitrogen (TN), generation of reduction products, current efficiency (CE) and energy consumption (EC) at different operating conditions. Under the catalysis of Co3O4/Ti, NO3- was reduced to N2 and NH4+, while no NO2- was produced. After the introduction of chloride ions and IrO2-RuO2/Ti as the anode, the NH4+ was selectively oxidized to N2. The removal efficiencies of NO3--N (at 100 mg/L) and TN after 2 h were 91.12% and 60.25%, respectively (pH 7.0; Cl- concentration, 2000 mg/L; current density, 15 mA/cm2). After 4 hours of operation, NO3--N and TN were completely removed. However, considering the EC and CE, a two-hour reaction was the most appropriate. The EC and CE were 0.10 kWh/g NO3-N and 40.3 %, respectively, and electrocatalytic performance was maintained after 10 consecutive reduction cycles (2 h each). The cathode Co3O4/Ti, which prepared by electrodeposition, can effectively remove NO3--N, with low EC and high CE.